Molecular density regulating electron transfer efficiency of S. oneidensis MR-1 mediated roxarsone biotransformation. (July 2020) - Wang, Gang; Han, Neng; Liu, Li; Ke, Zhengchen; Li, Baoguo; Chen, Guowei
Abstract: Efficient extracellular electron transport is a key for sufficient bioremediation of organoarsenic pollutants such as 4-hydroxy-3-nitrobenzenearsonic acid (roxarsone). The related apparent kinetics characteristics are essential for engineering practice of bioremediation activities and for full understanding the environmental fate of roxarsone, yet remains poorly understood. We report, to our knowledge, the first study of the electron transfer characteristics between roxarsone and participating S. oneidensis MR-1. The electron transfer rate during roxarsone biotransformation was estimated up to 3.1 × 10 6 electrons/cell/s, with its value being clearly associated with the apparent roxarsone concentration. Lowing roxarsone concentration extended the average separation distance between cells and neighboring roxarsone molecules and thereby augmented electric resistance as well as extended cell movement for foraging, thus reduced electron transfer rate. In addition, the presence of roxarsone significantly stimulated population growth of S. oneidensis MR-1 with nearly doubled maximum specific growth rate, albeit with clearly increased lag time, as compared with that of none-roxarsone scenario. These findings provide, at the first time, basic biostoichiometry of S. oneidensis MR-1 induced roxarsone biotransformation, which may shed lights for full understanding of roxarsone transformation process in waste treatment systems that are necessary for engineering practice and/or environmental risks assessment. Graphical abstract: Image 1 Highlights: Roxarsone stimulated population growth of S. oneidensis MR-1. Roxarsone maximum specific reduction rate decreased with increasing roxarsone. Bacterial electron transfer rate was estimated up to 1.4 × 10 6 electrons/cell/s. Bacterial electron transfer rate increased with present roxarsone concentration. Abstract : Main findings: We reported a first study of the electron transfer characteristics between roxarsone and partnering S. oneidensis MR-1. Molecular density of roxarsone regulated electron transfer efficiency of S. oneidensis MR-1 mediated roxarsone biotransformation.